ON "THE NATURAL NATURE OF NATURALISM": ANSWERS TO JOHN HEDLEY BROOKE'S QUESTIONS: with Mark Harris, "Apocalypses Now: Modern Science and Biblical Miracles: The Boyle Lecture 2018"; John Hedley Brooke, "The Ambivalence of Scientific Naturalism: A Response to Mark Harris"; and Mark Harris, "On 'the Natural Nature of Naturalism': Answers to John Hedley Brooke's Questions.". Issue 4 (21st November 2018) - Harris, Mark
Abstract: In John Hedley Brooke's response to my 2018 Boyle Lecture he provided some helpful prompts to sharpen my position on naturalism, and posed two further questions to me. This article takes up his prompts, and offers some answers to his questions, especially concerning the Resurrection of Jesus.